2022
DOI: 10.3390/biomedicines10081814
|View full text |Cite
|
Sign up to set email alerts
|

A nop56 Zebrafish Loss-of-Function Model Exhibits a Severe Neurodegenerative Phenotype

Abstract: NOP56 belongs to a C/D box small nucleolar ribonucleoprotein complex that is in charge of cleavage and modification of precursor ribosomal RNAs and assembly of the 60S ribosomal subunit. An intronic expansion in NOP56 gene causes Spinocerebellar Ataxia type 36, a typical late-onset autosomal dominant ataxia. Although vertebrate animal models were created for the intronic expansion, none was studied for the loss of function of NOP56. We studied a zebrafish loss-of-function model of the nop56 gene which shows 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The combined data from the nop56 -deficient zebrafish provide a model in which nop56 is essential for erythropoiesis in zebrafish, although no anemia cases have been reported to be related to a nop56 mutation. A recent nop56 sa12582 zebrafish line generated using the ENU method showed severe neurodegeneration characterized by the absence of the cerebellum, significantly reduced numbers of spinal cord neurons, and impaired motor functions with high levels of p53 -dependent apoptosis in the central nervous system [ 21 ], which is consistent with our results. Additionally, we found that erythroid cell maturation was impaired in our nop56 mutants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The combined data from the nop56 -deficient zebrafish provide a model in which nop56 is essential for erythropoiesis in zebrafish, although no anemia cases have been reported to be related to a nop56 mutation. A recent nop56 sa12582 zebrafish line generated using the ENU method showed severe neurodegeneration characterized by the absence of the cerebellum, significantly reduced numbers of spinal cord neurons, and impaired motor functions with high levels of p53 -dependent apoptosis in the central nervous system [ 21 ], which is consistent with our results. Additionally, we found that erythroid cell maturation was impaired in our nop56 mutants.…”
Section: Discussionsupporting
confidence: 91%
“…The expansion of a hexanucleotide repeat in intron 1 of NOP56 causes a novel type of dominant cerebellar ataxia, spinocerebellar ataxia type 36 [ 19 , 20 ]. Dysfunction of nop56 in zebrafish induces a severe neurodegenerative syndrome [ 21 ]. However, there is little research to elucidate the function of NOP56 in blood development in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A study in zebrafish found that NOP56 heterozygous mutants exhibited severe neurodegenerative phenotypes, including cerebellar loss, reduced number of spinal neurons, and motor impairment. NOP56 homozygous mutants show increased apoptosis and early death in zebrafish ( 76 ). The study found that the mRNA expression of the ZPLD1 gene was reduced in NOP56 homozygous mutants, and the reduced expression of ZPLD1 was associated with balance dysfunction ( 77 ).…”
Section: Nop56 and Spinocerebellar Ataxia Type 36mentioning
confidence: 99%
“…The authors aimed at establishing a better understanding of NOP56's role in the normal functioning and development of the central nervous system. They used various innovative methods and found that NOP56 loss of function causes a severe neurodegenerative phenotype characterized by early death, increased apoptosis, absence of cerebellum, a reduced numbers of spinal cord neurons and impaired movement [4]. Tighilet et al reviewed animal models of peripheral vestibulopathies of different types and stages of vestibular pathologies [5].…”
mentioning
confidence: 99%